A Comparative Analysis on Fully Integrated Spectral Broadening of Kerr Frequency Combs - Jing Wang; Yuhao Guo; Henan Liu; Guifang Li; Lin Zhang (IEEE Photonics Journal, 2017)
Microresonator-based frequency combs have potential to achieve on-chip frequency metrology. To obtain high-power comb lines at f and 2f for self-referenced stabilization, we evaluate the feasibility of building a fully integrated comb generator with spectral broadening. Comparing two types of nonlinear waveguides based on Si and chalcogenides, we find that the system feasibility relies on integrated waveguide amplifiers. If with a high-gain amplifier, a dispersion-engineered chalcogenide waveguide is preferred. Otherwise, an Si waveguide performs better. Considering the immaturity of both on-chip amplification technologies for ultrafast pulses and hybrid integration of multiple nonlinear materials, it could be concluded that in near future it is not practical to achieve fully on-chip f-2f self-referenced comb stabilization via subsequent spectral broadening of a Kerr frequency comb. Alternatively, direct generation of octave-spanning Kerr combs via dispersion engineering still remains attractive.